Evaluation of SaRIF High‐Energy Electron Reconstructions and Forecasts. Issue 12 (24th November 2021) - Glauert, S. A.; Horne, R. B.; Kirsch, P.
Abstract: Increasing numbers of satellites are orbiting through the Earth's radiation belts, and the range of orbits being commonly used is also growing. As a result, there is an increasing need for services to help protect satellites from space weather. The Satellite RIsk prediction and radiation Forecast (SaRIF) system provides reconstructions and forecasts of the high‐energy electron flux throughout the outer radiation belt and translates these predictions into charging currents, dose rates, total ionizing dose and risk indicators. SaRIF both informs satellite operators of current and expected conditions and provides a tool to aid in post‐event analysis. The reconstructions and forecasts are provided by the British Antarctic Survey Radiation Belt Model (BAS‐RBM) running as part of an automatic system using real‐time data to specify the boundary conditions and drive processes within the physics‐based model. If SaRIF is to provide a useful tool, then the accuracy of the reconstructions and forecasts needs to be understood. Here we assess the accuracy of the simulations for geostationary orbit by comparing the model output with measurements made by the GOES 14 spacecraft for the period March–September 2019. No GOES 14 data was used to create the reconstruction or forecasts. We show that, with some improvements to the original system, the reconstructions have a prediction efficiency of 0.82 for >800 keV electrons and 0.87 for >2 MeV electrons, with corresponding prediction efficiencies of 0.59 and 0.78 for the forecasts. Plain Language Summary: The number of satellites orbiting the Earth is steadily increasing. Many of these satellites pass through the Earth's radiation belts where they may encounter high‐energy electrons that could potentially damage the satellite. The levels of these high‐energy electrons can vary by orders of magnitude depending on conditions in space, but actual observations of these electrons from space are sparse. As a result, there in an increasing need for services that alert satellite operators to hazardous conditions and provide a means of understanding the radiation environment when a satellite anomaly has occurred. The Satellite Risk prediction and radiation Forecast (SaRIF) system provides one such service. SaRIF uses the British Antarctic Survey Radiation Belt Model (BAS‐RBM) and real‐time data to simulate the Earth's radiation belts, providing reconstructions of the state of the radiation belts in the past and forecasts 24 hr ahead. This paper assesses the accuracy of the reconstructions and forecasts by comparing them with data measured independently by the GOES 14 spacecraft. We show that for the period from 1 March to 1 September 2019 there is reasonable agreement between the model and measured data, and that the agreement increases when some improvements are introduced into the SaRIF modeling. Key Points: SaRIF provides forecasts and reconstructions of the high‐energy ( E > ∼100 keV) electron flux across the radiation belts Prediction efficiencies of 0.87 for reconstructions of >2 MeV electrons at geostationary orbit Prediction efficiencies of 0.78 for forecasts of >2 MeV electrons 1 day ahead at geostationary orbit